Global Existence and Blow-Up for the Euler-Bernoulli Plate Equation with Variable Coefficients. (24th December 2014) - Hao, Jianghao; Lan, Jie
Abstract : We prove the local existence, blow-up, global existence, and stability of solutions to the initial boundary value problem for Euler-Bernoulli plate equation with variable coefficients.